Association between polymorphisms of thymidylate synthase gene 5′- and 3′-UTR and gastric cancer risk: meta-analysis. Issue 6 (23rd December 2016) - Mo, Ao; Zhao, Yongliang; Shi, Yan; Qian, Feng; Hao, Yingxue; Chen, Jun; Yang, Shiwei; Jiang, Yuxing; Luo, Ziyan; Yu, Peiwu
Abstract : Gastric cancer is the most common cancer and the most frequent cause of cancer death worldwide. Several studies have identified the role of thymidylate synthase (TS) 5′- and 3′-UTR and gastric cancer susceptibility; however, the results still remain inconclusive. The purpose of this meta-analysis was to reinvestigate this correlation. In the present study, online databases were searched to retrieve relevant articles published between January 2000 and 2016. The odds ratio (OR) and 95% confidence interval (CI) were employed to calculate the strength of association. Overall, a total of 13 articles were screened out, including 2382 gastric cancer patients and 3171 healthy controls. We found that polymorphisms of TS 5′-UTR 2R (double repeats)/3R (triple repeats) of a 28-bp sequence (11 articles) and 3′-UTR del6/ins6 (seven articles) were not significantly associated with increased risk of gastric cancer. Subgroup analysis by ethnicity showed that 2R allele and 2R/2R genotype in TS 5′-UTR were associated with gastric cancer susceptibility in Caucasian and African populations; del6 allele, del6/del6 and del6/ins6 genotypes were correlated with gastric cancer in Caucasian population. In conclusion, our result suggested that TS polymorphisms might be the risk factors for gastric cancer risk in Caucasian population, although this association needs further study, and future large-scale researches are still required.